Notch-mediated conversion of activated T cells into stem cell memory-like T cells for adoptive immunotherapy - Kondo, Taisuke (Nat Commun, 2017)
Adoptive T-cell immunotherapy is a promising approach to cancer therapy. Stem cell memory T (T(SCM)) cells have been proposed as a class of long-lived and highly proliferative memory T cells. CD8(+) T(SCM) cells can be generated in vitro from naive CD8(+) T cells via Wnt signalling; however, methods do not yet exist for inducing T(SCM) cells from activated or memory T cells. Here, we show a strategy for generating T(SCM)-like cells in vitro (iT(SCM) cells) from activated CD4(+) and CD8(+) T cells in mice and humans by coculturing with stromal cells that express a Notch ligand. iT(SCM) cells lose PD-1 and CTLA-4 expression, and produce a large number of tumour-specific effector cells after restimulation. This method could therefore be used to generate antigen-specific effector T cells for adoptive immunotherapy.